Human skeletal remains: a field guide to identification, recovery, and preservation - White, Teresa A. (CRC Press, Taylor & Francis Group, 2026)
"Human Skeletal Remains is a step-by-step field guide to teach proper recovery techniques when a forensic anthropologist is unavailable for immediate scene responses. In the absence of a forensic anthropologist, the investigator assumes the responsibility of ensuring the complete and accurate recovery of skeletal materials from scenes. This could be problematic if the investigator has not had specialized training in human remains recoveries. To help investigators carry out this task, the authors developed this guide using 328 full-color demonstrative photos with easy-to-follow instructions on how to identify and recover human skeletal remains using scientifically defensible methods. It is an excellent resource for law enforcement, medicolegal death investigators, CSIs, anthropologists, medical examiners, coroners, evidence recovery technicians, students, and other forensic professionals. Human Skeletal Remains is an illustrative tool designed to accompany you on scene. Use it to identify the bones you locate, then follow the instructions to recover them. Get it dirty!"-- Provided by publisher